Los cuentos infantiles en el desarrollo de la inteligencia emocional en las niñas y niños de 4 años del nivel inicial II de la unidad educativa Dr. Manuel Agustín Cabrera Lozano, de la ciudad de Loja, periodo 2014-2015 - Cuenca Saritama, Ludy Josefina (2016)
This research includes a study of children's stories in the development of emotional intelligence in children 4 years of initial level II of the Education Unit Dr. Manuel Agustin Cabrera Lozano, of the city of Loja, 2014-2015. The general objective we help develop emotional intelligence through children's stories in girls and children 4 years of Initial Level II of the Education Unit Dr. Manuel Agustin Cabrera Lozano, of the City of Loja, 2014-2015. during the investigation the following method methods scientific, synthetic analytical, hermeneutical, statistical, development of research begins with the application of the technique of direct observation and the instrument used to collect the data was the observation guide used, the same that allowed us to evaluate the development of emotional intelligence of children, the population studied was 22 children. The results obtained after applying the observation guide emotional intelligence we have 6 children corresponding to 27% have an acceptable emotional intelligence because fair to share and 16 children corresponding to 73% have an emotional intelligence is not very well developed and they do not like sharing therefore concludes that activities should help develop emotional intelligence conducting activities children's stories.